Electric Field Analysis of Linear Low-Density Polyethylene (LLDPE)-NR Biocomposite Using FEMM Software - Ghazalee, Muhammad Ariff Izuddin; Mohd Jamail, Nor Akmal (Evolution in Electrical and Electronic Engineering, 2023)
In the development of future electrical networks, it is crucial to develop new alternative insulating materials that can improve the performance of the next-generation high-voltage cables. The high electric field reduces the resistance of solid insulation and causes partial discharge that occurs through the impurities in a dielectric where this phenomenon causes ageing of the dielectric and ultimately leads to breakdown. Thus, this project seeks to analyze the electric field intensity of Low Linear Density Polyethylene (LLDPE) when added with 2.5%, 5.0%, 7.5% and 10.0% of different types of bio-filler such as pineapple leaves fibre, and oil palm empty fruit bunch. This can be achieved by creating a two-dimensional (2D) axisymmetric electrostatic model by using the Finite Element Method Magnetics (FEMM) 4.2 software. The results showed that the inclusion of bio-filler in LLDPE increased the maximum electric field intensity when compared with unfilled LLDPE. The electric field intensity also varied with the different weight percentages of biocomposite and their permittivity. As a result, the maximum electric field intensity was much lower for LLDPE added with a 2.5% loading of the pineapple leaves fibre. As an outcome, pineapple leaf fibre was the best composition because at the top sphere electrode than other compositions it has a lower electric field intensity, which tends to improve dielectric properties.